Performance analysis of the RSS value for the video transmission using Wifi network / Hibatul Azizi Hisyam Ng - Hisyam Ng, Hibatul Azizi (2016)
Wifi coverage is frequently being an issue in any household with internet services subscriber. As to ensure user gain mobility when using the internet services, Wifi is consider as the best medium to be used in most premises be it in small houses like apartments until the spacious office floor area. In this thesis, the studies continue to investigate the quality of Wifi coverage in average double story houses and how the Receive Signal Strength (RSS) value affects the performance of the services. It is found out that, for the lowest Direct Sequence Spread Spectrum DSSS 1 Mbps, the maximum acceptable RSS value is -95 dBm. The highest Direct Sequence Spread Spectrum (DSSS) 11 Mbps permits maximum RSS value of -88dBm while for the Orthogonal Frequency Division Multiplex (OFDM) 6 Mbps the maximum acceptable value is -91 dBm. The highest Orthogonal Frequency Division Multiplex (OFDM) 54 Mbps, the maximum permitted RSS value is reduced to -72dBm as a conclusion, the RSS value is reduced upon the increment of the bandwidth.